The Double-Edged Sword—How Human Papillomaviruses Interact With Immunity in Head and Neck Cancer - Wang, Hao-fan; Wang, Sha-sha; Tang, Ya-Jie; Chen, Yu; Zheng, Min; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Immunology, 2019)
Patients with HPV-associated head and neck squamous cell carcinoma (HNSCC) have remarkably better prognosis. The tumors differ from HPV-negative OPSCC with respect to clinical, genomical, molecular and immunological aspects, especially having the characteristics of high levels of immune cell infltration and high degrees of immunosuppression. This review will summarize immune evasion mechanisms in HPV-positive HNSCC, analyze the host various immune responses to HPV and abundant numbers of infiltrating immune cell, and difference between HPV-positive HNSCC with cervical cancer will be discussed. A deeper understanding of the immune landscape will help new concepts to emerge in immune-checkpoint oncology, which might be a valuable add-on to established concepts.